2021
DOI: 10.1002/ptr.7141
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Xiyanping injection in the treatment of COVID‐19: A multicenter, prospective, open‐label and randomized controlled trial

Abstract: Xiyanping (XYP) is a Chinese herbal medicine used in the clinic to treat respiratory infection and pneumonia. Recent evidence identified XYP as a potential inhibitor of severe acute respiratory syndrome coronavirus 2, implying XYP as a possible treatment for the coronavirus disease 2019 (COVID‐19). Here, we conducted a prospective, multicenter, open‐label and randomized controlled trial to evaluate the safety and effectiveness of XYP injection in patients with mild to moderate COVID‐19. We consecutively recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 27 publications
4
73
2
2
Order By: Relevance
“…Twenty-four RCTs reported the generation of random sequences, of which three RCTs [ 12 , 26 , 29 ] described the performance of allocation concealment. Two RCTs [ 12 , 29 ] blinded participants and researchers as well as outcome evaluators. Twenty-nine RCTs completely reported the data of each primary outcome, including lost to follow-up and withdrawal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four RCTs reported the generation of random sequences, of which three RCTs [ 12 , 26 , 29 ] described the performance of allocation concealment. Two RCTs [ 12 , 29 ] blinded participants and researchers as well as outcome evaluators. Twenty-nine RCTs completely reported the data of each primary outcome, including lost to follow-up and withdrawal.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of 7 RCTs [ 11 , 12 , 16 , 18 , 19 , 22 , 23 ] demonstrated that TCM could observably lessen the proportion of patients progressing to severe cases [RR = 0.45, 95% CI (0.29, 0.68), I 2 = 0%, P = 0.0002] (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eligible participants were at least 18 years old and diagnosed with COVID-19 infection by Real-Time Polymerase Chain Reaction (RT-PCR) test. According to the definition of mild COVID-19 used in previous work (Zhang et al, 2021), we included only patients who had normal chest radiography by the time of hospital admission. In contrast, individuals who did not have chest radiography results received antiviral drugs (i.e., favipiravir) or received systemic corticosteroids on the first day of admission were excluded.…”
Section: Design Setting and Study Populationmentioning
confidence: 99%
“…Li et al [55] using network bioinformatics analysis based on clinical knowledge prioritized AGL (among 30 candidates) as a potentially effective COVID-19 repurposable drug. Interestingly, Zhang et al [56] in his clinical trial showed that injection with Xiyanping (XYP), a Chinese herbal compound (composed of 9-dehydro-17-hydro-andrographolide and sodium 9-dehydro-17-hydro-andrographolide-19-yl sulfate) improves and recovers COVID-19 patients having mild and moderate symptoms. Today, advancement with the laboratory and pharmacological studies focusing on AGL as a herbal bio-active compound has accelerated huge verified data with scientific outputs establishing its potential immune protective role in combating such viral outbreaks.…”
Section: Effectiveness Of Andrographolide (Agl) With New Emerging Viruses and Their Frequent Mutant Counterparts (Sars-cov-2 And Covid-19mentioning
confidence: 99%